2013
DOI: 10.1073/pnas.1218335110
|View full text |Cite
|
Sign up to set email alerts
|

Role of orthopyroxene in rheological weakening of the lithosphere via dynamic recrystallization

Abstract: For plate tectonics to operate on a terrestrial planet, the surface layer (the lithosphere) must have a modest strength (Earth, ≤200 MPa), but a standard strength profile based on olivine far exceeds this threshold value. Consequently, it is essential to identify mechanisms that reduce the strength of the lithosphere on Earth. Here we report results of high-strain laboratory deformation experiments on a representative olivine-orthopyroxene composition that show the addition of orthopyroxene substantially reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…Our new estimate of the activation energy thus implies that the rheology of oceanic lithosphere is not well represented by that of pure olivine aggregates. In fact, a recent laboratory experiment suggests that the presence of a secondary phase such as orthopyroxene is important for rheological weakening (Farla et al, 2013), and our estimate of ∼100 ± 50 kJ mol −1 (or 225 ± 112 kJ mol −1 for dislocation creep) may represent the 'effective' activation energy for such polymineralic aggregates. Whereas the results of our geoid inversion themselves do not distinguish between diffusion and dislocation creep, we suspect that dislocation creep would be more appropriate to explain the inferred occurrence of SSC around the fracture zones.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Our new estimate of the activation energy thus implies that the rheology of oceanic lithosphere is not well represented by that of pure olivine aggregates. In fact, a recent laboratory experiment suggests that the presence of a secondary phase such as orthopyroxene is important for rheological weakening (Farla et al, 2013), and our estimate of ∼100 ± 50 kJ mol −1 (or 225 ± 112 kJ mol −1 for dislocation creep) may represent the 'effective' activation energy for such polymineralic aggregates. Whereas the results of our geoid inversion themselves do not distinguish between diffusion and dislocation creep, we suspect that dislocation creep would be more appropriate to explain the inferred occurrence of SSC around the fracture zones.…”
Section: Discussionsupporting
confidence: 46%
“…So far proposed mechanisms include the feedback between shear localization and grain size evolution (Kameyama et al, 1997;Braun et al, 1999;Landuyt et al, 2008), the pre-existing zone of weakness such an oceanic fracture zone (Toth and Gurnis, 1998;Hall et al, 2003;Gurnis et al, 2004), the higher water content of oceanic lithosphere (e.g. Regenauer-Lieb et al, 2001), hydration by thermal cracking (Korenaga, 2007), and rheological weakening by a secondary orthopyroxene phase (Farla et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In these cracks, phase mixing cannot result from a two-stage-process involving first the formation of the small grains, and then a mixing process by, e.g., grain boundary sliding (GBS) as proposed by Farla et al (2013) and Linckens et al (2014). The nature of the local mixture also excludes dynamic recrystallization.…”
Section: Phase Mixing and Nucleationmentioning
confidence: 99%
“…Many studies have pointed out the presence of minor phases, such as micas or pyroxenes, as a condition for small grain sizes during grain-size-sensitive creep (Hiraga et al, 2010;Herwegh et al, 2011;Farla et al, 2013;Linckens et al, 2014;Platt, 2015). Most of them attributed the reduction of grain size to a combination of dynamic recrystallization and grain boundary sliding (GBS), resulting in phase mixing.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the secondary phase like pyroxenes can cause Zener pinning and slows down the kinetics of grain growth, resulting in the weakening of material and strain localization in the mylonite (Linckens et al 2011;Farla et al 2013). The small-grained area in the Hundskjeften peridotite does not contain much opx (less than 5%) but it has high cpx content (33% and 45%), which might have contributed to reduce grain growth in the mylonite by Zener pinning of cpx, which is believed to result in the shear localization in the peridotite.…”
Section: The Mechanism Of Shear Localizationmentioning
confidence: 99%